Georgian experience in the field of education and cultural policy: the example of the first democratic republic of Georgia in the years 1918 -1921 - Darchashvili, Manana (Journal of Education Culture and Society, 2021)
Aim. The paper aims to study and present the issue of Georgian education,   analyze it chronologically and thematically based on past experience. The paper deals with the period of the First Republic of Georgia, 1918-1921, and highlights the place of education and culture in Georgian politics. Moreover, the paper is focused on the connections of modern Georgian politics and the centuries-old traditional heritage and its transformation into the present reality.Method. The paper is presented based on a number of researched documents, empirical material, scientific research papers, monographs, analysis of government documents, historical-comparative method.            Result. The paper presents the reality of the first democratic republic in Georgia in 1918-1921, the effective steps of the state for the development of proper education and cultural policy, and its introduction and development in practice.            Conclusion. Several empirical materials prove that during the period of the First Republic of Georgia (1918-1921), despite the difficult political situation in Georgia, education in Georgia, with the support of the government and due to the active and creative work of representatives of such field as education, literature, theater, music, cinema, and science. were well developed. This issue is part of the country's internal policy, which is important and relevant today.